Role of ASIC1a in Aβ-induced synaptic alterations in the hippocampus. (May 2018) - Mango, D.; Nisticò, R.
Graphical abstract: Abstract: Acid-sensing ion channels (ASICs) are widely expressed in the mammalian central nervous system where they play a key role in synaptic transmission and in specific forms of memory. On the other hand, ASICs can be persistently active under pathological conditions contributing to neuronal damage in ischemic stroke, brain trauma, epilepsy and Parkinson's disease. However, to date no experimental evidence has linked ASICs to Alzheimer's disease (AD). Aim of the present work was to investigate, in CA1 pyramidal neurons, the possible involvement of ASIC1a in the Aβ-mediated effect on metabotropic glutamate (mGlu) receptor dependent transmission. We found that, in slices pretreated with Aβ, the pharmacological blockade of ASIC1a restored the increased intrinsic excitability following group I mGlu receptor activation. This suggests that, under certain conditions, ASIC1a might further contribute to the Aβ-related depolarizing response. We have recently demonstrated that ASIC1a is also involved long-term depression (LTD) induced either by low-frequency stimulation or by application of the group I mGlu receptor agonist DHPG. Here, we have shown that psalmotoxin-1, a selective blocker of ASIC1a, rescued the DHPG-LTD facilitation associated with genetic and non-genetic models of AD. Overall, these results suggest that a functional coupling between ASIC1a and mGlu receptors occurs and might contribute to the synaptic alterations associated with AD.